Crecimiento de tres cultivares de fique (furcraea sp.) en vivero (2020)
The evaluation of the growth of leaves, root and bulb of three cultivars of fique (sisal) Furcraea macrophylla, F. cabuya and F. castilla in the nursery, was carried out at the Universidad Nacional de Colombia, Sede Medellín, at 1520 meters above sea level, with average annual rainfall 1600 mm and mean annual temperature of 23 ° C and relative humidity between 70 and 80% corresponding to the pre-montane moist life zone (PMm). The nursery was established in bags, an Andisol from the south of the Aburrá Valley was used .The bulblets were sown 5 cm deep. The number and size of the leaves, bulb diameter, number and length of roots and biomass were measured monthly. Sprouting started three weeks after sowing. After the second month, a marked increase in biomass was observed, with a higher proportion of the leaves, the bulb accumulates biomass after the third month. The foliar emission rate is initially high on average 1 leaf, every 12 days, subsequently 1 leaf every 5-6 weeks. The leaves reach 49 cm in length and the roots 53 cm. F. castilla was the highest growth. Seedlings suitable for transplantation are obtained after four months.